A novel drug interaction between busulfan and blinatumomab. (January 2019) - Sweiss, Karen; Quigley, John G; Oh, Annie; Lee, Jonathan; Ye, Rosa; Rondelli, Damiano; Patel, Pritesh
Busulfan is an alkylating agent used in pre-transplant conditioning for patients undergoing hematopoietic stem cell transplantation. Several factors contribute to variations in busulfan drug disposition including bioavailability, age, liver function, genetic polymorphisms, and concurrent administration of other drugs. Busulfan is metabolized by hepatic oxidation via the cytochrome P450 3A4 system as well as through conjugation with glutathione. Interactions with drugs such as phenytoin, itraconazole, and metronidazole have been reported to alter busulfan clearance and result in sub- or supra-therapeutic concentrations. We report a case of a clinically significant drug interaction between intravenous busulfan and the bifunctional T-cell engager, blinatumomab, observed through busulfan therapeutic drug monitoring. We found that busulfan clearance was reduced resulting in a higher area under the concentration-time curve when it was administered 48 h after blinatumomab. Repeat busulfan pharmacokinetic testing two weeks later demonstrated increased clearance of the drug and a 31% higher dose recommendation. Similar to other protein therapeutics, cytokine elevations during blinatumomab treatment can lead to cytochrome 3A4 suppression. We hypothesize that the increased busulfan levels observed could be related to a cytokine-mediated CYP3A4 suppression. This represents a unique pharmacologic consideration in hematopoietic stem cell transplantation which would impact several drugs that undergo CYP3A4 metabolism, including calcineurin inhibitors, cyclophosphamide, sirolimus, and triazole antifungals. Additionally, this mechanism of CYP3A4 suppression may be relevant in treatments and disease states where cytokine levels are elevated such as haploidentical stem cell transplantation, graft-versus-host disease, and use of chimeric antigen receptor T-cell therapy.